Production of 2,5-furandicarboxylic acid from glucaric acid Using a Hybrid Catalyst System
Patent Information
- Application Number
- KR1020250048358
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2026-10-21
Smart Images

Figure PAT00012_ABST
Abstract
Description
Technology Field
[0001] The present disclosure relates to a method for producing 2,5-furandicarboxylic acid from glucaric acid using a hybrid catalyst system, and more specifically, to providing a hybrid catalyst system based on the structural interaction between an ionic liquid and an acid catalyst, and a method for producing 2,5-furandicarboxylic acid (FDCA) from glucaric acid using the hybrid catalyst system. Background Technology
[0002] As demands for carbon emission reduction due to climate change increase, the development of carbon-neutral alternative materials is actively underway to address the problem of excessive carbon dioxide emissions from petroleum-based industries. Lignocellulose-based biomass is a carbon-neutral resource composed of cellulose, hemicellulose, and lignin, and the concept of a biorefinery to produce high-value-added chemicals from it has been proposed.
[0003] Among these, 2,5-furandicarboxylic acid (FDCA) is a compound in which two carboxyl groups are introduced to a furan ring and can be used as a raw material for bio-based polymers such as polyamides and polyesters. In particular, polyethylene furanoate (PEF) derived from FDCA is attracting attention as a high-performance bioplastic that can replace existing petroleum-based PET (polyethylene terephthalate).
[0004] Conventional FDCA production has primarily been carried out through the oxidation reaction of biomass-derived 5-hydroxymethylfurfural (5-HMF). However, 5-HMF is structurally unstable and easily decomposes or condenses under moist and acidic conditions, causing problems such as reduced yield and the generation of byproducts during the concentration and purification processes. Consequently, existing FDCA manufacturing processes utilizing 5-HMF as a precursor have limitations in commercialization.
[0005] Therefore, attempts have been made to manufacture FDCA from more stable precursors.
[0006] Recently, the production of FDCA using aldaric acid, particularly glucaric acid, as a starting material has been proposed. Glucaric acid can be converted into FDCA through dehydration and cyclization reactions in the presence of an acid catalyst, and has the advantage of being more stable against moisture and acid compared to 5-HMF. However, in previous studies, high concentrations of strong acids such as sulfuric acid, hydrobromide, and p-toluenesulfonic acid were used in excess. This resulted in low FDCA yields, as well as difficulties in recovering and reusing the catalyst after the reaction is complete, and increased costs due to the complexity of the neutralization and treatment processes within the process.
[0007] To address this, the introduction of heterogeneous catalysts has been proposed, offering the advantage of ensuring reusability through solid-state catalysts. However, heterogeneous catalysts have limited contact efficiency with reactants due to the low mobility of functional groups immobilized on the catalyst surface. Consequently, catalytic activity is reduced, and reaction efficiency is lower compared to homogeneous catalysts, limiting their ability to replace existing processes.
[0008] Therefore, there is a need to develop a reusable catalyst system that maintains strong catalytic activity in the production of FDCA through the cyclization reaction of glucaric acid. Prior art literature
[0009] (Patent Document 0001) US 2017-0144982 A1 The problem to be solved
[0010] Accordingly, the inventors propose a hybrid catalyst system that simultaneously satisfies the high reactivity of homogeneous catalysts and the reusability of heterogeneous catalysts, namely, a hybrid catalyst system combining an ionic liquid and an acid catalyst. This system is formed through an in-situ reaction between an imidazole-based ionic liquid and a hydrohalic acid, and can simultaneously secure reusability and catalytic activity through an internally stable ionic interaction structure.
[0011] One embodiment provides a method for efficiently producing 2,5-furandicarboxylic acid (FDCA) by dehydrating and cyclizing glucaric acid in the presence of a hybrid catalyst system formed by an in-situ reaction of an imidazole compound and a hydrohalic acid.
[0012] Another embodiment provides a method for producing 2,5-furandicarboxylic acid (FDCA) by dehydrating and cyclizing glucaric acid in high yield in the presence of a hybrid catalyst system that has excellent catalytic activity and is reusable, using glucaric acid as a starting material. means of solving the problem
[0013] One embodiment provides a method for producing 2,5-furandicarboxylic acid, comprising the step of dehydrating and cyclizing glucaric acid in the presence of a hybrid catalyst system formed by an in-situ reaction of an imidazole represented by the following chemical formula 1 and a hydrohalic acid represented by chemical formula 2 to produce 2,5-furandicarboxylic acid (FDCA).
[0014] [Chemical Formula 1]
[0015]
[0016] [Chemical Formula 2]
[0017]
[0018] In the above chemical formulas 1 and 2, R is a C1-C10 alkyl and X is a halogen.
[0019] The above hybrid catalyst system may be prepared by the step of in-situ reaction of the imidazole of Formula 1 and the hydrohalic acid of Formula 2, followed by heating and drying.
[0020] The above hybrid catalyst system may induce a cyclization reaction by selectively dehydrating the hydroxyl groups at the C2 and C5 positions of glucaric acid.
[0021] The hydrohalic acid of Formula 2 above can be used in excess of the imidazole of Formula 1.
[0022] The hydrohalic acid of Formula 2 above can be used in an amount of 1.1 to 3 moles per 1 mole of the imidazole of Formula 1.
[0023] The above heating and drying may be performed in an oven at 40 to 70°C.
[0024] The above imidazole may be 1-methylimidazole, and the above hydrohalic acid may be hydrobromide.
[0025] The above glucaric acid may be glucaric acid monopotassium salt.
[0026] The concentration of glucaric acid in the above hybrid catalyst system may be 1% to 30% by weight.
[0027] The above reaction can be carried out at a temperature of 140 to 170°C.
[0028] The above manufacturing method may further include the step of introducing an anti-solvent to precipitate 2,5-furandicarboxylic acid (FDCA) and filtering the result to separate 2,5-furandicarboxylic acid (FDCA) and a hybrid catalyst system.
[0029] The above antisolvent may be water.
[0030] It may further include the step of purifying the precipitated 2,5-furandicarboxylic acid (FDCA) with activated carbon.
[0031] The above-described separated hybrid catalyst system can be regenerated through drying.
[0032] The above-mentioned regenerated hybrid catalyst system may further include the step of treating it with a cation exchange resin. Effects of the invention
[0033] According to the present invention, 2,5-furandicarboxylic acid (FDCA) can be produced by efficiently dehydrating and cyclizing glucaric acid in the presence of a hybrid catalyst system formed by an in-situ reaction of 1-alkylimidazole and a hydrohalic acid. In particular, the hybrid catalyst system possesses superior selectivity and reusability compared to existing strong acid systems through the maintenance of acid catalyst activity and the formation of stable interaction structures within the catalyst system. This allows for the resolution of problems arising from existing 5-HMF-based FDCA production methods.
[0034] According to the present invention, the limitations of 5-HMF are overcome by using glucaric acid as a stable precursor, and the catalyst system can be separated through a simple separation process after the reaction due to the hybrid catalyst system formed by the in-situ reaction of 1-alkylimidazole and a hydrohalic acid. In addition, the separated catalyst system has excellent reusability and enables efficient FDCA production.
[0035] In addition, the generated FDCA can be separated and purified to a high purity through aqueous solvent precipitation and activated carbon purification, and the catalyst system can be regenerated through cation exchange resin treatment, thereby optimizing FDCA production through cost reduction and an environmentally friendly process. Accordingly, the present invention suggests that it can overcome the limitations of existing 5-HMF-based technology and be very useful as a new bioplastic monomer production process using glucaric acid as a starting material. Brief explanation of the drawing
[0036] Fig. 1 - (a): FT-IR spectra of NMI, HBr, and ILCA, (b): Thermogravimetric analysis results of ILCA (ILCA: hydrobromide-based hybrid catalyst system prepared in Preparation Example I ([Hmim][Br] + HBr, NMI:HBr = 1:2, molar ratio) Fig. 2 - Results of FDCA production derived from glutaric acid according to reaction temperature (Reaction time: 60 min, Glucaric acid concentration: 20 wt%) Fig. 3 - Results of FDCA production derived from glutaric acid according to reaction time (glucaric acid concentration: 20 wt%) Fig. 4 - Results of FDCA production derived from glutaric acid according to glutaric acid concentration (Reaction temperature: 160℃, Reaction time: 60 min) Fig. 5 - FDCA yield according to manufacturing conditions of the hybrid catalyst system ((a) FDCA yield and pH change of the hybrid catalyst system according to change in molar ratio of NMI and HBr, (b): FDCA yield and pH change of the hybrid catalyst system according to change in drying time under molar ratio (NMI:HBr = 1:2) condition) Fig. 6 - FDCA production results according to the type of acid catalyst in the hybrid catalyst system ((a) changes in FDCA yield, pH, and glucaric acid conversion rate according to the type of acid catalyst in the hybrid catalyst system, (b) ratio of glucaric acid to glucaric acid lactone according to the type of acid catalyst in the hybrid catalyst system) Fig. 7 - (a) Results of reuse of the hydrobromite-based hybrid catalyst system, (b) Color change of the hydrobromite-based hybrid catalyst system and images of precipitated KBr crystals according to the number of reuses, (c) Results of ionic composition analysis of the precipitated crystals Fig. 8 - Photos of precipitated FDCA before and after purification and 1 H-NMR results ((a): before purification, (b): after purification) Specific details for implementing the invention
[0037] Unless otherwise defined in this specification, all technical and scientific terms have the same meaning as generally understood by those skilled in the art to which the present invention pertains. The terms used in the description herein are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention.
[0038] The singular form used in this specification is intended to include the plural form unless specifically indicated otherwise in the context.
[0039] Throughout this specification, the terms “comprising,” “having,” “containing,” or “having” any component mean that, unless specifically stated otherwise, other components are not excluded but may be included, and do not exclude elements, materials, or processes not additionally listed.
[0040] The numerical ranges used herein include lower and upper limits and all values within the range, increments logically derived from the form and width of the defined range, all of which are limited, and all possible combinations of upper and lower limits of the numerical range defined in different forms. Unless otherwise specifically defined in this specification, values outside the numerical range that may occur due to experimental error or rounding are also included in the defined numerical range.
[0041] Unless otherwise specifically defined in this specification, “about” may be considered to be a value within 30%, 25%, 20%, 15%, 10%, or 5% of the specified value.
[0042] The present disclosure will be described in detail below. However, this is merely illustrative and the present disclosure is not limited to the specific embodiments described illustratively.
[0043] One embodiment relates to a method for producing 2,5-furandicarboxylic acid from glucaric acid using a hybrid catalyst system, comprising the step of producing 2,5-furandicarboxylic acid (FDCA) by dehydrating and cyclizing glucaric acid in the presence of a hybrid catalyst system formed by an in-situ reaction of an imidazole represented by Chemical Formula 1 and a hydrohalic acid represented by Chemical Formula 2.
[0044] [Chemical Formula 1]
[0045]
[0046] [Chemical Formula 2]
[0047]
[0048] In the above chemical formulas 1 and 2, R is a C1-C10 alkyl and X is a halogen.
[0049] Conventional FDCA production processes rely on the oxidation reaction of 5-hydroxymethylfurfural (5-HMF). However, 5-HMF is unstable to heat and acid, which can lead to decomposition or condensation reactions during processes such as storage, concentration, and purification, thereby degrading the yield and quality of FDCA. This drawback has been one of the main factors limiting the efficiency of FDCA production in existing technologies. Accordingly, the present invention aims to produce FDCA using glucaric acid as a more stable precursor. Glucaric acid exhibits superior resistance to moisture and acid compared to 5-HMF, enabling stable FDCA production and offering the advantage of resolving various problems that may occur during the process.
[0050] In particular, the present invention produces FDCA using a hybrid catalyst system formed through an in-situ reaction of an imidazole and a hydrohalic acid. This hybrid catalyst system possesses unique characteristics that allow it to function as both a catalyst and a reaction medium. That is, while acting as a reaction medium, the strong acid catalyst is generated "in-situ" to maximize reactivity, and simultaneously, the catalyst is easily separated and reusable after the reaction. This is an important factor in solving the problems of catalyst separation and recycling that occur in conventional strong acid catalyst systems, and the reusability of the catalyst in the process of the present invention is a significant advantage that enhances economic efficiency and sustainability. This method ensures the efficient use of the catalyst and allows for the optimization of FDCA production in a more stable and sustainable manner.
[0051] The above hybrid catalyst system may be prepared by the step of in-situ reaction of the imidazole of Formula 1 and the hydrohalic acid of Formula 2, followed by heating and drying.
[0052] The above hybrid catalyst system can induce a cyclization reaction by selectively dehydrating the hydroxyl groups at the C2 and C5 positions of glucaric acid. Specifically, the cyclization reaction of glucaric acid is promoted by the dehydration reaction occurring at the C2 and C5 positions where two hydroxyl groups (-OH) are present. The strongly acidic environment generated in this hybrid catalyst system causes hydrogen ions (H₂) from the hydroxyl groups at the C2 and C5 positions. + By removing ) , dehydration reactions are induced at these positions. The dehydrated hydroxyl groups are converted into electronically stable 2,5-furandicarboxylic acid (FDCA) in the subsequent reaction, and in this process, the hybrid catalyst system enables the efficient conversion of glucaric acid. This selective dehydration reaction is a key process for increasing the yield of FDCA production and plays an important role in stably converting glucaric acid in a strongly acidic environment.
[0053] The hydrohalic acid of Formula 2 above may be used in excess with respect to the imidazole of Formula 1; specifically, the hydrohalic acid of Formula 2 above may be used in an amount of 1.1 to 3 moles, or 1.125 to 3 moles, or 1.25 to 3 moles, or 1.5 to 3 moles, or 1.5 to 2.5 moles per 1 mole of the imidazole of Formula 1. Within the molar ratio ranges described above, the ionic liquid and residual hydrohalic acid formed by the reaction between the imidazole and the hydrohalic acid can form stable interactions to realize maximized catalytic activity. Therefore, by adjusting the molar ratio within the ranges described above, the stability and reactivity of the catalyst system can be optimized. In particular, it is possible to maintain the required acidity (strongly acidic environment) while avoiding the use of excessive acid, which can contribute to increasing the efficiency of the catalyst and maximizing its reusability.
[0054] The above-mentioned heating and drying may be performed in an oven at 40 to 70°C, or at 40 to 60°C, or at 45 to 55°C, and the drying time may be 5 hours or more, or 10 hours or more, or 12 hours or more, or 18 hours or more, or less than 100 hours. Under these drying conditions, excess moisture within the hybrid catalyst system is effectively removed, allowing the ionic liquid resulting from the reaction between the imidazole and the hydrohalic acid and the residual hydrohalic acid to form a stable interaction. This ensures the maximization of catalytic activity and stable reaction performance. On the other hand, if the drying temperature is 100°C or higher, excessive volatilization of the hydrohalic acid occurs, causing the concentration of residual hydrohalic acid within the hybrid catalyst system to decrease. Consequently, the pH of the hybrid catalyst system rises, and as a result, the acid catalytic activity of the hybrid catalyst system is reduced, which may lead to a problem of a lower yield of FDCA.
[0055] The above imidazole may be 1-methylimidazole, and the above hydrohalic acid may be hydrobromide. In particular, a hydrobromide-based hybrid catalyst system can inhibit the lactonization of glucaric acid and provide a catalytic environment optimized for FDCA production through a selective dehydration reaction.
[0056] Since aldaric acid is produced by the oxidation of the C1 and C6 positions of an aldose, various types of aldaric acid can be produced depending on the structure of the original aldose. Therefore, it is reasonable to consider the availability of the aldose when selecting aldaric acid. In this context, given that glucose, the precursor of glucaric acid, is a C6 sugar abundant in nature, the glucaric acid that is the raw material for FDCA may be glucaric acid monopotassium salt.
[0057] The concentration of glucaric acid in the above hybrid catalyst system may be 1 to 30 wt%, or 1 to 20 wt%, or 1 to 10 wt%, or 3 to 10 wt%. Within the ranges described above, the glucaric acid concentration can provide an optimal concentration capable of promoting an efficient cyclization reaction in the reaction. Since reaction efficiency decreases if the concentration is too low and unnecessary byproducts may be generated due to an excess of reactants if the concentration is too high, the present invention can achieve a stable FDCA yield within this range.
[0058] The above reaction may be carried out at a temperature of 140 to 170°C, or 140 to 160°C, or 150 to 160°C, and the reaction time may be 10 minutes or more, or 30 minutes or more, or 1 hour or more, and 3 hours or less, or 2 hours or less. The reaction temperature within the above-described range is optimized to promote the efficient dehydration and cyclization reaction of glucaric acid. Below 140°C, the reaction rate slows down, and above 170°C, side effects such as reduced FDCA yield and decreased catalytic activity may occur due to excessive thermal decomposition.
[0059] The above method for producing 2,5-furandicarboxylic acid may further include the step of introducing an anti-solvent to precipitate 2,5-furandicarboxylic acid (FDCA) and filtering the result to separate 2,5-furandicarboxylic acid (FDCA) and a hybrid catalyst system.
[0060] The above-mentioned antisolvent may be water. That is, the FDCA produced after the reaction can be separated by precipitation using water as the antisolvent. In this process, the hybrid catalyst system remains dissolved in the aqueous solution, which facilitates the separation and reuse of the catalyst. The hybrid catalyst system, which has high solubility in water, can be easily separated after the reaction, enabling the efficient reuse of the catalyst.
[0061] The method may further include the step of purifying the separated 2,5-furandicarboxylic acid (FDCA) with activated carbon, thereby enabling recovery with high purity. The purification process using activated carbon adsorbs impurities from the FDCA, thereby effectively obtaining high-purity FDCA.
[0062] The above-described separated hybrid catalyst system can be regenerated through drying. For example, the separated hybrid catalyst system can be reused after removing excess moisture by drying at a temperature of 40 to 70°C, or 40 to 60°C, or 45 to 55°C for 10 hours or more, or 12 hours or more, or 18 hours or more, or 20 hours or more, or 30 hours or more, or 40 hours or more, or 50 hours or more, and less than 100 hours, or less than 90 hours, or less than 80 hours, or less than 70 hours, or 60 hours or less. This process ensures efficient regeneration of the catalyst and allows the physical and chemical properties of the catalyst to be maintained stably after the reaction.
[0063] The method may further include the step of treating the above-mentioned regenerated hybrid catalyst system with a cation exchange resin. K derived from the raw material glucarate monopotassium salt + As ions continuously accumulate within the hybrid catalyst system, catalyst performance may deteriorate. Therefore, a cation exchange resin is used to [remove] K accumulated in the hybrid catalyst system. + H ions - By replacing with ions, the acidity of the catalyst can be restored and the catalyst's activity regenerated, thereby maintaining or improving the FDCA yield. Through this regeneration process, the catalyst can be reused repeatedly, and the efficiency of FDCA production can be maximized as an economical and sustainable process.
[0064] The aforementioned hybrid catalyst system is reusable and regenerable, thereby ensuring both process sustainability and economic efficiency. In addition, the generated FDCA can be precipitated and purified to a high purity, which can also increase the efficiency of the post-treatment process.
[0065] The present invention will be described in more detail below through examples. These examples are intended solely to explain the invention more specifically, and it will be obvious to those skilled in the art that the scope of the invention is not limited by these examples according to the gist of the invention.
[0066] [ingredient]
[0067] Standard potassium glucarate salt (98%, Sigma-Aldrich Co. (St. Louis, MO, USA)) was used as the raw material for FDCA. 1-methylimidazole (NMI, 99%) and hydrobromic acid (HBr, 47-49%) were purchased from Samchun Pure Chemicals Co., Ltd. (Pyeongtaek, South Korea). In addition, to compare the effects of anions on FDCA production, hydrofluoric acid (HF, 48%, Sigma-Aldrich Co.), hydroiodic acid (HI, 57%, Thermo Fisher Scientific (Waltham, MA, USA)), hydrochloric acid (HCl, 35-37%, Samjeon Soonyak Industrial Co.), and sulfuric acid (70%, Samjeon Soonyak Industrial Co.) were used.
[0068] [Analysis Method]
[0069] FT-IR Analysis: Fourier transform infrared spectroscopy (FT-IR) analysis of ILCA was performed using a Nicolet iS50 FTIR spectrometer (Thermo Fisher Scientific, USA) and an attenuated total reflectance (ATR) attachment. 4000 to 500 cm⁻¹ -1 256 scans were performed per sample within the range, and the resolution was 4.0 cm. -1 It was set to.
[0070] NMR analysis: Identification of the intermediate during the reaction was performed using a 600-MHz nuclear magnetic resonance (NMR) spectrometer (ADVANCE 600, Bruker, Germany), which is equipped with a 14.095 T superconducting 51-mm Bohr magnet and a 5 mm BBO BB-H&F-D CryoProbe Prodigy.
[0071] Thermogravimetric Analysis (TGA): Thermogravimetric analysis of ILCA was performed using a Tarsus TG 209 thermogravimetric analyzer (NETZSCH, Germany). Before scanning, the sample was held at 105°C for 10 minutes to remove physically absorbed water. Subsequently, the temperature was scanned from 105°C to 800°C at a rate of 20°C / min in a nitrogen atmosphere (N2 flow rate: 40 mL / min).
[0072] HPLC Analysis: Glucaric acid and FDCA were analyzed using high-performance liquid chromatography (HPLC, 1260 Infinity, Agilent, CA, USA) equipped with an Aminex 87H column (Eluent: 0.005 N sulfuric acid, Oven temperature: 50℃, Flow rate: 0.1 mL / min, Injection volume: 10 μL). Peaks were identified by comparing the retention times of each peak, and peak concentrations were determined by comparing them with the standard calibration curves of each chemical.
[0073] Ion Chromatography (IC) Analysis: Cations (K + ) and anions (Br - The concentration of ) was analyzed using an ion chromatography instrument (ICS-3000, Thermo Dionex, CA, USA). The instrument was equipped with a Dionex IonPac AS20 column (4 × 250 mm) and a column guard (Dionex IonPac AG20, 4 × 50 mm), and sodium hydroxide was used as the solvent. The flow rate was set to 1 mL / min, and the column temperature was maintained at 30°C. Cations and anions were analyzed using a conductivity detector at a detector temperature of 35°C.
[0074] GC-MS Analysis: Byproduct analysis was performed using a gas chromatograph (GC, Agilent 7890B, Agilent Technologies, Inc., Santa Clara, CA, USA) equipped with a DB-624 column (20 m × 180 μm × 1 μm) and a mass spectrometer (MS, Agilent 5977A). The oven temperature was maintained at 50°C for 5 minutes, then raised to 240°C at a heating rate of 4°C / min, and maintained at this temperature for 10 minutes. The injector and FID temperatures were set to 200°C and 270°C, respectively. The injector split ratio was set to 1:15, and chemical compounds were quantified using a NIST mass spectrometer.
[0075] Preparation Example I: Preparation of a Hybrid Catalyst System
[0076] To prepare a hybrid catalyst system, 1-methylimidazole (NMI) and various acid catalysts (HX) were mixed. Hydrobromide (HBr), hydrofluoric acid (HF), hydrochloric acid (HCl), hydroiodide (HI), and sulfuric acid (H2SO4) were used as acid catalysts (HX). 1-methylimidazole (NMI) and acid catalysts (HX) were mixed in a molar ratio ranging from 1:1 to 1:3 and stabilized by stirring at room temperature. Subsequently, the mixture was dried in a 50°C oven for approximately 54 hours until no further weight change occurred to remove excess moisture contained in the acid catalysts. Afterward, the prepared hybrid catalyst system was cooled to room temperature and stored in a sealed container to prevent deterioration due to moisture absorption and exposure to air.
[0077] Characterization of Hydrobromide-Based Hybrid Catalyst Systems
[0078] FT-IR analysis and thermogravimetric analysis (TGA) were performed to evaluate the structural changes and thermal stability of the hydrobromide-based hybrid catalyst system ([Hmim][Br] + HBr, NMI:HBr = 1:2, molar ratio) prepared in Preparation Example I.
[0079] FT-IR analysis was performed to confirm structural changes (Fig. 1(a)). The C=N peak of 1-methylimidazole (NMI) is at approximately 1515 cm⁻¹. -1 It was observed at, and in the hybrid catalyst system prepared by adding hydrobromide (HBr) at a 2 molar ratio, the intensity of the corresponding peak decreased, and at 1585 cm⁻¹ -1 A new NH vibration peak was identified in the vicinity. This indicates that the nitrogen of NMI has been protonated, implying that a stable hybrid catalyst system was formed through the interaction with residual HBr simultaneously with the formation of [Hmim][Br]. Additionally, the strength of the CN bond within the imidazole ring was reduced, suggesting that interactions with the acid catalyst exist even within the ring structure.
[0080] Thermogravimetric analysis (TGA) was performed to confirm thermal stability (Fig. 1(b)). A slight weight loss was observed in the range of approximately 100 to 200°C, attributed to the volatilization of moisture contained in hydrobromide and some HBr. Subsequently, major thermal decomposition occurred in the range of approximately 220 to 300°C, and specifically, derivative thermogravimetry (DTG) analysis revealed that the maximum thermal decomposition rate was observed at approximately 287°C. Considering that the individual components of 1-methylimidazole (NMI, bp: 198°C) and hydrobromide (HBr, bp: 122°C) have relatively low boiling points, the stable interaction between [Hmim][Br] and residual HBr within the hybrid catalyst system suppresses the volatility of the individual components with low boiling points, thereby indicating that the thermal stability of the entire system has been improved.
[0081] Example I: Production of Glucaric Acid-Derived FDCA Using a Hydrobromide-Based Hybrid Catalyst System
[0082] A certain amount of monopotassium glucarate salt was added to a glass tube reactor with a capacity of 20 mL and equipped with a Teflon screw cap, and then 2.5 g of a hydrobromide-based hybrid catalyst system (Preparation Example 1) was added. The reactor was sealed with the screw cap and then placed on a heating block (LI-HB111, LK LAB Korea) preheated to the target reaction temperature to carry out the reaction for a set reaction time. After the reaction was completed, the reactor was cooled to room temperature.
[0083] The above hydrobromide-based hybrid catalyst system was prepared by mixing 1-methylimidazole and hydrobromide (HBr) in a molar ratio of 1:2 in Preparation Example 1 and then drying at 50°C (Preparation Example I).
[0084] After the reaction was completed, the product was diluted in dimethyl sulfoxide (DMSO), and the yield of the generated 2,5-furandicarboxylic acid (FDCA) was analyzed using high-performance liquid chromatography (HPLC). Specifically, the change in FDCA yield according to reaction temperature, reaction time, and glucaric acid concentration (2.5-30 wt%) in the presence of a hybrid catalyst system (based on 2.5 g) was evaluated, and the results are shown in Figures 2 to 4.
[0085] Figure 2 illustrates the yield of 2,5-furandicarboxylic acid (FDCA) and the conversion rate of glucaric acid according to the reaction temperature. It can be seen that the FDCA yield increases rapidly when the reaction temperature is 140°C or higher, and reaches a maximum yield (approximately 58%) at 160°C. Additionally, it can be seen that the conversion rate of glucaric acid is maintained at over 90% in the reaction temperature range of 140°C to 160°C.
[0086] Figure 3 shows the change in FDCA yield according to reaction time, and it can be seen that the maximum FDCA yield (approx. 69.5%) is reached at 60 minutes at a reaction temperature of 160℃, and then shows a decreasing trend over time.
[0087] Figure 4 shows the FDCA yield according to changes in glutaric acid concentration, and it can be seen that a relatively high FDCA yield was observed in the low range of glutaric acid concentrations of 2.5 to 5 wt%, and in particular, the maximum yield (approx. 69.5%) was observed at 5 wt%.
[0088] Example II: Evaluation of the yield of glucaric acid-derived FDCA according to the manufacturing conditions of a hydrobromide-based hybrid catalyst system
[0089] To evaluate the effect of manufacturing conditions of a hydrobromide-based hybrid catalyst system on the production of 2,5-furandicarboxylic acid (FDCA) derived from glucaric acid, hybrid catalyst systems were prepared by varying the mixing molar ratio of 1-methylimidazole (NMI) and hydrobromide (HBr) and the drying time, respectively.
[0090] A hybrid catalyst system was prepared by mixing 1-methylimidazole (NMI) and hydrobromide (HBr) in a molar ratio ranging from 1:1 to 1:3 in reference to Preparation Example I above, and then drying at 50°C for 0 to 72 hours. The acidity (pH) of each prepared hybrid catalyst system was measured using a pH meter (Orion Star A211, Thermo Fisher Scientific) after dissolving the prepared hybrid catalyst system in distilled water at a concentration of 0.01 M.
[0091] Each prepared hybrid catalyst system (2.5 g) and glucarate monopotassium salt (Sigma-Aldrich, 98%) (5 wt%) were placed in a 20 mL Teflon screw-cap glass tube, sealed, and then placed in a heating block preheated to 160°C for 1 hour. After the reaction was finished, the reactor was cooled to room temperature, and the product was diluted in dimethyl sulfoxide (DMSO) to analyze the FDCA yield by high-performance liquid chromatography (HPLC). The results are shown in Fig. 5.
[0092] Figure 5(a) illustrates the FDCA yield and pH changes of the hybrid catalyst system according to changes in the molar ratio of NMI and HBr, confirming that the maximum FDCA yield is observed at a molar ratio of 1:2. Specifically, when the NMI:HBr molar ratio was 1:1, the pH was high at approximately 6 due to the neutralization reaction, and the FDCA yield was low. On the other hand, when the NMI:HBr molar ratio was 1:1.125 or higher, the pH decreased rapidly to 2.95 or lower, indicating that the acid catalyst effect was manifested. Consequently, the FDCA yield increased sharply from 1:1.25 or higher, and it was confirmed that the FDCA yield reached its maximum (approximately 69.5%) under the 1:2 condition.
[0093] Figure 5(b) illustrates the FDCA yield and pH changes according to drying time and drying temperature of a hybrid catalyst system ([Hmim][Br] + HBr, NMI:HBr = 1:2 molar ratio). It was confirmed that when dried at 50°C for more than 18 hours, the pH remained stable, and in particular, when dried for more than 36 hours, the FDCA yield reached a maximum value (approximately 69.5%). This is attributed to the effective removal of excess moisture within the catalyst system, which led to the formation of stable interactions between [Hmim][Br] and HBr. On the other hand, even with the same drying time, when the drying temperature was increased to 105°C, excessive volatilization of hydrobromide (HBr) occurred, causing a decrease in the HBr concentration within the catalyst system and consequently, an increase in the pH of the catalyst system. As a result, the formation of stable interactions between [Hmim][Br] and residual HBr was inhibited, leading to a decrease in the acid catalytic activity of the hybrid catalyst system and ultimately a significant decrease in the FDCA yield from glucaric acid.
[0094] [Comparative Example 1] FDCA production results using 1-methylimidazole (NMI) alone
[0095] The experiment was conducted in the same manner as in Example II, except that 1-methylimidazole (NMI) alone was used instead of the hybrid catalyst system. The reaction was carried out at 160°C for 1 hour, and glucarate monopotassium salt was used at a concentration of 5 wt%.
[0096] As a result, almost no FDCA was produced (Fig. 5(a)), which is presumed to be because when NMI is used alone, it exhibits strong basicity with a pH of about 10.5, thus failing to function as an acid catalyst, and consequently, the acid-catalyzed cyclization reaction of glucaric acid was inhibited. These results suggest that the acidic conditions of the hybrid catalyst system according to the present invention are essential reaction conditions for FDCA production.
[0097] [Comparative Example 2] FDCA production results using hydrobromide (HBr) alone
[0098] The experiment was conducted in the same manner as in Example II, except that hydrobromide (HBr) alone was used instead of the hybrid catalyst system. The reaction was carried out at 160°C for 1 hour, and glucarate monopotassium salt was used at a concentration of 5 wt%.
[0099] As a result, some FDCA was produced, but a significantly lower yield (about 40%) was observed compared to when the hybrid catalyst system of the present invention was used (Fig. 5(a)). This is presumed to be because the excess water present in the reaction system when hydrobromide was used alone interfered with the dehydration and cyclization reactions of glucaric acid.
[0100] In particular, the pH of the HBr-only system was found to be approximately 1.9, which means that despite having sufficient acidity as an acid catalyst, it failed to induce an efficient cyclization reaction of glucaric acid. Therefore, it is difficult to obtain a high FDCA yield as in the present invention with the presence of a simple acid catalyst alone, and it was confirmed that a hybrid catalyst system having stable interactions between [Hmim][Br] and HBr plays a decisive role in the high-yield FDCA production from glucaric acid.
[0101] Example III: Evaluation of FDCA Yield According to the Type of Acid Catalyst in the Hybrid Catalyst System
[0102] The production efficiency of 2,5-furandicarboxylic acid (FDCA) derived from glucaric acid was evaluated according to the type of acid catalyst (HX) among the components of the hybrid catalyst system.
[0103] The acid catalysts used were hydrofluoric acid (HF), hydrochloric acid (HCl), hydroiodic acid (HI), and hydrobromide (HBr). Each acid catalyst was mixed with 1-methylimidazole (NMI) in a 1:2 molar ratio and dried in an oven at 50°C for 54 hours to prepare hybrid catalyst systems ([Hmim][X] + HX, NMI:HX = 1:2 molar ratio, X=F, Cl, I, Br). Each prepared catalyst system (2.5 g) was reacted with monopotassium glucarate salt (concentration: 5 wt%) at a reaction temperature of 160°C and a reaction time of 1 hour. The yield of the FDCA produced after the reaction was analyzed by high-performance liquid chromatography (HPLC). The results are shown in Fig. 6.
[0104] Figure 6(a) shows the FDCA yield, glucaric acid conversion rate, and pH changes according to the type of acid catalyst. Figure 6(b) shows the results of quantifying the proportion of glucaric acid existing in the lactone form within various acid catalyst-based hybrid catalyst systems using 1H-NMR analysis. The hydrobromide (HBr)-based hybrid catalyst system exhibited a high FDCA yield of approximately 69.5%, and the glucaric acid conversion rate was also close to 100%, demonstrating the best reaction efficiency. The hydrochloric acid (HCl) and hydroiodide (HI)-based hybrid catalyst systems showed relatively low FDCA yields, which is analyzed to be due to the relatively high proportion of glucaric acid existing in the lactone form under the respective acid catalysts, thereby inhibiting the cyclization reaction to FDCA. On the other hand, the hydrofluoric acid (HF)-based hybrid catalyst system had a high pKa of the acid itself and maintained a relatively high pH due to strong interactions between fluoride anions and hydrogen ions, which reduced its activity as an acid catalyst and consequently resulted in almost no FDCA production.
[0105] The above results suggest that the structural state and reaction selectivity of glucaric acid vary depending on the type of acid catalyst, and in particular, that a hydrobromide-based hybrid catalyst system is most suitable for the selective production of FDCA through the inhibition of lactonization and the selective dehydration of C2 / C5 hydroxyl groups.
[0106] [Comparative Example 3] Production of FDCA using a sulfuric acid-based hybrid catalyst system
[0107] The reaction was carried out under the same conditions as in Example III, except that a hybrid catalyst system prepared by mixing 1-methylimidazole (NMI) and sulfuric acid (H2SO4) in a molar ratio of 1:2 was used.
[0108] As a result, the conversion rate of glucaric acid was high, but the yield of FDCA remained at approximately 26.3% (Fig. 6(a)). Similar to the hydrobromide-based hybrid catalyst system, the sulfuric acid-based hybrid catalyst system showed a low formation rate of glucaric acid lactones, but the FDCA yield remained at a significantly low level (approximately 26.3%) (Fig. 6(b)). This is attributed to the fact that the strong dehydrating ability of sulfuric acid caused excessive removal of water within the reaction system, leading to the breakdown of the hydrogen bond network between glucaric acid molecules and the subsequent existence of glucaric acid in a clustered form. These glucaric acid clusters induce condensation reactions rather than cyclization reactions, and as the reaction proceeds, aromatic byproducts such as benzocyclopropene are formed, significantly reducing the selectivity of FDCA. GC / MS analysis also revealed the highest content of aromatic byproducts compared to other acid catalysts.
[0109] In other words, although the sulfuric acid-based hybrid catalyst system had sufficient acidity, it failed to induce the selective cyclization reaction of glucaric acid in terms of reaction selectivity, resulting in a low FDCA yield.
[0110] [Comparative Example 4] Production of FDCA by separate addition of ionic liquid ([Hmim][Br]) and acid catalyst (HBr)
[0111] For comparison with the hybrid catalyst system of the present invention, a catalyst system was configured by separately adding 1-methylimidazolium bromide ([Hmim][Br]) and hydrobromide (HBr), and FDCA was prepared from glucaric acid under the same conditions as in Example III (reaction temperature 160°C, reaction time 1 hour, glucaric acid concentration 5 wt%). At this time, the moles of 1-methylimidazole and hydrobromide added were set to be the same as in Example III.
[0112] As a result, a simple mixed catalyst system in which 1-methylimidazolium bromide ([Hmim][Br]) and hydrobromide (HBr) were added as individual components showed an FDCA yield of about 58.4%, whereas the hydrobromide (HBr)-based hybrid catalyst system used in Example III ([Hmim][Br] + HBr, NMI:HBr = 1:2 molar ratio) showed a yield of about 69.5%.
[0113] These differences in yield clearly demonstrate that even when the same catalyst components are used, catalytic activity can vary significantly depending on the method of manufacturing the catalyst system (in-situ formation vs. simple mixing). In other words, the hybrid catalyst system of the present invention can provide a more uniform and strong acidity within the catalyst system by forming structurally stable interactions between 1-methylimidazole and HBr through an in-situ reaction and drying process. This stable acidic environment effectively promotes the selective cyclization reaction of glucaric acid, thereby enabling the achievement of a high FDCA yield.
[0114] On the other hand, it is analyzed that a catalyst system consisting of a simple mixture of [Hmim][Br] and HBr exhibits incomplete interaction between the ionic liquid and the acid catalyst, resulting in reduced catalytic activity and decreased efficiency in the cyclization reaction of glucaric acid. Therefore, it has been proven that the structural stability of the catalyst system and the manufacturing process play a key role in the selective production of FDCA.
[0115] Example IV: Reuse of Hydrobromide-Based Hybrid Catalyst System and Separation and Purification of FDCA
[0116] The reusability of the hydrobromide (HBr)-based hybrid catalyst system and the possibility of efficient separation and purification of the generated FDCA were evaluated.
[0117] A hydrobromide-based hybrid catalyst system (2.5 g), prepared by mixing 1-methylimidazole (NMI) and hydrobromide (HBr) in a 1:2 molar ratio and drying in a 50°C oven for 54 hours, was reacted with monopotassium glucarate salt (concentration: 5 wt%) at a reaction temperature of 160°C for 1 hour. To separate the product FDCA, 5 mL of distilled water was added to the reaction mixture as an anti-solvent after the reaction was completed to separate FDCA, which has low solubility in water, in the form of a precipitate, and to dissolve the hydrobromide-based hybrid catalyst system, which has a high affinity for water, in an aqueous solution. The precipitated solid was separated by filtration after precipitation at 4°C for 12 hours, and the hydrobromide-based hybrid catalyst system dissolved in the aqueous solution was reused after removing excess moisture by drying in a 50°C oven for about 54 hours.
[0118] Using a separated hydrobromide-based hybrid catalyst system, the FDCA yield, pH, and Br were reused up to a total of 5 times under the same reaction conditions (glucaric acid concentration 5 wt%, hydrobromide-based hybrid catalyst 2.5 g, reaction temperature 160℃, reaction time 1 hour), and the FDCA yield, pH, and Br were compared according to the number of reuses. - Changes in content were checked. The results are shown in Fig. 7.
[0119] The hydrobromide-based hybrid catalyst system maintained catalytic activity up to the third reuse, but the FDCA yield decreased from the fourth use onwards, and the yield plummeted to 44% by the fifth use (Fig. 7(a)). This is attributed to K from the raw material, glucarate monopotassium salt. + It is determined that the continuous accumulation of ions within the hybrid catalyst system and their reaction with bromide ions formed KBr crystals, and that the precipitation of these crystals within the hybrid catalyst system inhibited the acid catalytic activity of the hybrid catalyst system (Fig. 7(b)). Ion chromatographic analysis of the ionic composition of the precipitate revealed approximately 68% Br -and about 27% of K + It was confirmed that it is a potassium chloride (KBr) crystal composed of (Fig. 7(c)). In addition, Br in the hybrid catalyst system - The trend of decreasing content and increasing pH was consistent with the trend of inhibiting catalytic activity (Fig. 7(a)).
[0120] Accordingly, to regenerate the reusable hybrid catalyst system, accumulated K was used with a cation exchange resin (Amberlyst 15 hydrogen form-dry, Sigma-Aldrich Co.). + H ions - A regeneration process involving ion substitution was performed, and when the reaction was carried out again using this, the regenerated hybrid catalyst system recovered its catalytic activity and showed an FDCA yield similar to that of the initial system (Fig. 7(a), "Regenerated").
[0121] Meanwhile, to determine whether the purification of the FDCA precipitated through a precipitation process using purified water after the reaction ends affects the purity, the precipitated FDCA was separated by filtration, and an additional purification process was performed.
[0122] The isolated FDCA, before purification, was dark brown, and 1H-NMR analysis revealed numerous peaks in the 6.5–8 ppm range due to impurities other than FDCA (Fig. 8(a)). The purity of the precipitate was confirmed to be approximately 85%.
[0123] The separated FDCA was treated with activated carbon (AC) to adsorb and remove impurities, and after purification, the FDCA turned a color close to white and it was confirmed that most of the peaks originating from impurities were removed (Fig. 8(b)). The purity of the purified FDCA was found to be approximately 95.2% as a result of HPLC analysis.
[0124] It was confirmed that the hybrid catalyst system of the present invention can maintain catalytic activity even with repeated use. In addition, it was confirmed that the generated FDCA can be separated and purified to a high purity through the catalyst system and purification process of the present invention.
[0125] As described above, the present invention has been explained by specific details and limited embodiments; however, this is provided merely to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. Those skilled in the art can make various modifications and variations from this description.
Claims
Claim 1 A method for preparing 2,5-furandicarboxylic acid, comprising the step of dehydrating and cyclizing a glucaric acid in the presence of a hybrid catalyst system formed by an in-situ reaction of an imidazole represented by Chemical Formula 1 and a hydrohalic acid represented by Chemical Formula 2; [Chemical Formula 1] [Chemical Formula 2] In the above chemical formulas 1 and 2, R is a C1-C10 alkyl and X is a halogen. Claim 2 A method for producing 2,5-furandicarboxylic acid, wherein, in claim 1, the hybrid catalyst system is produced by the step of heating and drying after in-situ reaction of the imidazole of Formula 1 and the hydrohalic acid of Formula 2. Claim 3 A method for producing 2,5-furandicarboxylic acid, wherein, in claim 1, the hybrid catalyst system selectively dehydrates the hydroxyl groups at the C2 and C5 positions of glucaric acid to induce a cyclization reaction. Claim 4 A method for preparing 2,5-furandicarboxylic acid, wherein the hydrohalic acid of Formula 2 is used in excess with respect to the imidazole of Formula 1. Claim 5 A method for preparing 2,5-furandicarboxylic acid, wherein the hydrohalic acid of Formula 2 is used in an amount of 1.1 to 3 moles per 1 mole of imidazole of Formula 1. Claim 6 A method for producing 2,5-furandicarboxylic acid, wherein, in paragraph 2, the heating and drying is performed in an oven at 40 to 70°C. Claim 7 A method for preparing a 2,5-furandicarboxylic acid according to claim 1, wherein the imidazole is 1-methylimidazole and the hydrohalic acid is hydrobromide. Claim 8 A method for preparing 2,5-furandicarboxylic acid, wherein the glucaric acid is a glucaric acid monopotassium salt, according to claim 1. Claim 9 A method for producing 2,5-furandicarboxylic acid according to claim 1, wherein the concentration of glucaric acid in the hybrid catalyst system is 1% to 30% by weight. Claim 10 A method for producing 2,5-furandicarboxylic acid according to claim 1, wherein the reaction is carried out at a temperature of 140 to 170°C. Claim 11 A method for producing 2,5-furandicarboxylic acid according to claim 1, further comprising the step of introducing an anti-solvent to precipitate 2,5-furandicarboxylic acid (FDCA) and filtering the result to separate 2,5-furandicarboxylic acid (FDCA) and a hybrid catalyst system. Claim 12 A method for preparing 2,5-furandicarboxylic acid, wherein the antisolvent in claim 11 is water. Claim 13 A method for producing 2,5-furandicarboxylic acid, further comprising the step of purifying the separated 2,5-furandicarboxylic acid (FDCA) with activated carbon in claim 11. Claim 14 A method for producing 2,5-furandicarboxylic acid, wherein, in claim 11, the separated hybrid catalyst system is regenerated through drying. Claim 15 A method for producing 2,5-furandicarboxylic acid, further comprising the step of treating the regenerated hybrid catalyst system with a cation exchange resin in claim 14.